Exploring Visitors of Janji Jiwa Coffee Shop: An MBKM Program by Students of Indo Global Mandiri University - Hertati, Lesi; Asharie, Asmawati; Avini, Terti (International Journal of Social Science and Community Service, 2023)
Janji Jiwa is the most popular coffee shop, and South Sumatra is one of the provinces with the highest number of coffee drinkers and coffee shop visits nationally. Aligned with the research objectives, this article delves into consumption motives and the construction of a consumerist lifestyle among patrons of the Janji Jiwa coffee shop in Palembang City. The method employed is a qualitative approach, utilizing a single case study research type. Informant selection was carried out using purposive sampling, with the informants comprising both active consumers and observer participants. To ensure data validity and reliability, the researcher conducted a data triangulation test. A shift in consumption motives is identified, where consumption no longer solely fulfills biological needs but rather represents a form of self-actualization within the context of social significance and classification. The formation of an imaginary perspective and the construction of a consumerist lifestyle are intricately linked to complex and varied causal laws, considering aspects such as sign value, the social logic of consumption, social space, and media influence. These aspects are rich with simulations, manifested in both abstract and concrete forms. This fact serves as evidence of the rationality of contemporary society, as reflected in consumer behavior.